The association between the retail price of manufactured cigarettes and bidis on current smoking status in India - Radhika Nayak; Asha Kamath; Jinshuo Li; Muralidhar M. Kulkarni; Veena G. Kamath; Praveen Kumar; Ashwath Naik; Steve Parrott; Noreen D. Mdege (Tobacco Induced Diseases, 2022)
Introduction In India, the retail prices of bidis and cigarettes varied between the two Global Adult Tobacco Surveys (GATS) conducted in 2009–2010 and 2016–2017. The relationship between the retail price of smoked tobacco products and their use is unclear for India. Our study thus aimed to use available datasets to investigate the association between the retail price and current smoking status of bidis and cigarettes in India.